The Effect of the PBL Model on Literacy and Numeracy Skills in Acid-Base Material - Ratman Ratman; Kasmudin Mustapa; Dewi S. Ahmar; Anastasya Anastasya; Ijirana Ijirana; Magfirah Magfirah; Haeruddin Haeruddin (Universitas Tadulako, 2025)
Problem-Based Learning is a learning model that focuses primarily on problems in the learning process. It encourages students to collaborate in groups to solve problems through various activities. The purpose of this study was to determine the effect of the Problem-Based Learning (PBL) model on students' numeracy literacy skills in acid-base material. This study used a quantitative, true-experimental design. The research population consisted of 47 students. The research sample was obtained using purposive sampling, divided into an experimental class of 15 students from class XI MIA 2 and a control class of 16 students from class XI MIA 1. The research instruments included a literacy test comprising 20 multiple-choice questions and a numeracy test comprising five essay questions. Experts validated all instruments provided. Data analysis used the Mann-Whitney test. The results of the data analysis showed that the Mann-Whitney test p-value (0.000) was lower than the predetermined significance level of 0.05. Therefore, it can be concluded that the PBL learning model affects students' numeracy literacy skills.